Ensino simultâneo de mandos por informação manipulando operações motivadoras: uma replicação sistemática de Lemos (2017) - Morais, Flávia Maria Mascarenhas Veras (2022)
The mand for information is an important part of communication and it is difficult to establish it in people diagnosed with autism spectrum disorder (ASD). This study, which is a systematic replication of Lemos (2017), aims to: (a) verify the effectiveness of a simultaneous teaching procedure with a delay in the presentation time of the echoic model in the acquisition of the mands for information “Which?”, “Who ?” and “Where?”, under the conditions of motivating operations (establishing operation – EO; and abolishing operation – AO); and (b) assess the generalization of the emission of the mand “Which?” to other containers and of the mand “Where?” to other location. Two children with ASD underwent a five-phase procedure: (1) pre-assessment, to examine previous follow-up instruction skill repertoires; (2) baseline, with interspersed trials of the three commands, under mixed blocks with EO and AO conditions; (3) teaching of the three mands with a delay procedure in the presentation time of the echoic model of the mands for information, carried out in two stages: Step 1, the teaching of each mand separately; and Step 2, the teaching with mixed blocks, with randomized mands; (4) post-test, which was similar to the baseline, after each teaching step; and (5) generalization test of the use of “Which?” to other containers and “Where?” to other location. In the conclusion of the study, both participants emitted differential responses in the applied conditions, in randomized trials in both teaching and the generalization test. The child Flávio completed Stage 1 and having reached the criterion in the post-test, did not need to undergo Stage 2. Christiani reached the research criterion after the two stages. Convergent and divergent points about the participants’ data are discussed and the data are analyzed in comparison with Lemos (2017) and Shillingsburg et al. (2011)